Study of bone metabolism and angiogenesis in patients undergoing high‐dose chemotherapy/autologous hematopoietic stem cell transplantation. (4th December 2017) - Boutsikas, Georgios; Terpos, Evangelos; Papatheodorou, Athanasios; Tsirkinidis, Pantelis; Tsirigotis, Panayiotis; Meletiou, Anastasia; Lalou, Eleni; Telonis, Vasileios; Zannou, Anna; Kanellopoulos, Alexander; Galani, Zacharoula; Stefanou, Angeliki; et al.
Abstract: Objectives: As the interaction between hematopoietic stem cells (HSCs) and endosteal and endothelial niches in HSCs homing is essential, we aimed to study bone turnover and angiogenesis in 29 patients with lymphoma/multiple myeloma undergoing hematopoietic stem cell transplantation (HSCT). Methods: Serum samples were collected before high‐dose chemotherapy (HDT), at the end of HDT, after HSC infusion, at the nadir of myelotoxicity, and at engraftment. Bone metabolism (CTX, TRACP‐5b, bALP, OC, DKK1, RANKL, OPG), and angiogenesis (Ang1, Ang2) markers were measured. These markers were also measured in 21 control patients before and after conventional chemotherapy. Results and Conclusions: Bone resorption declined during HSCT (decrease in TRACP‐5b [ P  < .001] and CTX [ P  = .006]). Bone formation declined as well (decrease in bALP and OC [ P  < .001 for both]). RANKL/OPG ratio, an indicator of osteoclastic activation, did not change significantly ( P  = .5). Ang1/Ang2 ratio, a vessel equilibrium marker, decreased significantly ( P  < .001) suggesting endothelial destabilization. The changes observed in the control group were similar except of bALP and RANKL/OPG ratio. Moreover, Ang1/Ang2 ratio on the day after HSC infusion strongly correlated with time to neutrophil and platelet engraftment ( P  < .001 for both). Conclusively, bone turnover and vessel destabilization represent important events during HSCT probably reflecting the effect of chemotherapy.